FRS 16 implementation effects on financial statements and key financial ratios - Lopes, A.I.; Penela, D. (XXIII Grudis Conference and Doctoral Colloquium, 2024)
This study addresses the IFRS Foundation call for the real effects of IFRS 16 implementation on companies, particularly as a result of the elimination of the accounting treatment for operating leases, allowing for a more accurate inter-company comparison for stakeholders. IFRS 16 was projected to affect airlines, travel and leisure, and transport, the most. Thus, this study examines these businesses to see if IFRS 16 implementation affected financial statements elements and related key financial ratios. The study demonstrates a combined effect, a business-as-usual effect, and the isolated effect of IFRS 16 implementation, indicating that the distributions between them are not identical and that the statistically significant variations are primarily attributed to the isolated effect of IFRS 16. Therefore, assets, liabilities, operating income, the so-called EBITDA, and interest expenses increase, accompanied by significant changes in structure and liquidity ratios, but not in profitability measures. Yet, using fsQCA, it was possible to verify that different entity characteristics lead to higher or lower ROA/ROE. Furthermore, the interest coverage ratio was the only variable for which the comparison of the isolated effect of IFRS with other related effects was not statistically significant, but the combined effect is. This suggests that the simultaneous increases in EBITDA and interest expenses arising from business as usual and the isolated effects of IFRS 16 may cancel each other out, resulting in no change to this indicator.